The Role of Typography in Branding Strategy - Ifdal Irman; Heru Pranata (Jurnal Ilmiah Multidisiplin, 2025)
Typography plays a central role in contemporary branding strategies, transcending its aesthetic function to become a critical instrument of visual communication and brand differentiation. This study aims to examine the functions, elements, principles, as well as the psychological and strategic implications of typography in shaping a strong and consistent visual identity. Employing a descriptive-qualitative approach through literature review and case study analysis, the findings indicate that strategic typographic choices significantly influence consumer perception, message readability, and brand loyalty. The integration of typography with other branding elements, such as logos and color palettes, has been shown to enhance brand recognition across various platforms. This research also discusses current typography trends and the challenges of implementing inclusive design. Practical recommendations are provided to guide typography usage in branding strategies that are adaptive and audience-centered.